2013
DOI: 10.1016/j.cmet.2013.06.002
|View full text |Cite
|
Sign up to set email alerts
|

TXNIP Maintains the Hematopoietic Cell Pool by Switching the Function of p53 under Oxidative Stress

Abstract: Reactive oxygen species (ROS) are critical determinants of the fate of hematopoietic stem cells (HSCs) and hematopoiesis. Thioredoxin-interacting protein (TXNIP), which is induced by oxidative stress, is a known regulator of intracellular ROS. Txnip(-/-) old mice exhibited elevated ROS levels in hematopoietic cells and showed a reduction in hematopoietic cell population. Loss of TXNIP led to a dramatic reduction of mouse survival under oxidative stress. TXNIP directly regulated p53 protein by interfering with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
89
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 111 publications
(92 citation statements)
references
References 48 publications
3
89
0
Order By: Relevance
“…The expression levels were determined by western blotting and statistical analysis (Figure 1f,g and Supporting Information Figure S5) or quantitative real‐time PCR (Supporting Information Figure S1A,B). We previously reported the regulation of p53 by TXNIP (Jung et al, 2013). To examine the effects of p53 on the cellular senescence, we prepared WT, KO, p53 ‐/‐ , and TXNIP ‐/‐ p53 ‐/‐ (DKO) MEF cells.…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…The expression levels were determined by western blotting and statistical analysis (Figure 1f,g and Supporting Information Figure S5) or quantitative real‐time PCR (Supporting Information Figure S1A,B). We previously reported the regulation of p53 by TXNIP (Jung et al, 2013). To examine the effects of p53 on the cellular senescence, we prepared WT, KO, p53 ‐/‐ , and TXNIP ‐/‐ p53 ‐/‐ (DKO) MEF cells.…”
Section: Resultsmentioning
confidence: 95%
“…However, the interaction of TXNIP and AKT was upregulated by glucose and H 2 O 2 treatment (Figure 3), implying that TXNIP may negatively regulate AKT activity under glucose stress and oxidative stress. We previously reported that TXNIP deficiency induced premature aging phenotypes of HSCs in aged mice by increasing ROS levels in vitro and in vivo (Jung et al, 2016, 2013 ). Next, we analyzed the metabolic characterization of WT and KO mice to determine the effect of TXNIP on the aging of mice.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations